Dynesys system vs posterior decompression and fusion for the treatment of lumbar degenerative diseases. Issue 21 (22nd May 2020) - Wang, Hongbo; Peng, Jun; Zeng, Qingshen; Zhong, Yanchun; Xiao, Chunlin; Ye, Yongjun; Huang, Weimin; Liu, Wuyang; Luo, Jiaquan
Abstract: Background: The Dynesys dynamic stabilization system is an alternative to rigid instrumentation and fusion for the treatment of lumbar degenerative disease. The purpose of this study is to evaluate the clinical efficacy between Dynesys and posterior decompression and fusion for lumbar degenerative diseases. Methods: The computer was used to retrieve the Cochrane library, Medline, Embase, CNKI, Wanfang database and Chinese biomedical literature database; and the references and main Chinese and English Department of orthopedics journals were manually searched. All the prospective or retrospective comparative studies on the clinical efficacy and safety of Dynesys and posterior decompression and fusion were collected, so as to evaluate the methodological quality of the study and to extract the data. The RevMan 5.2 software was used for data analysis. Results: A total of 17 studies were included in the meta-analysis. There were no significant differences in Oswestry disability index and visual analogue score for leg pain, visual analogue score for back pain, L2–S1 ROM between Dynesys and fusion group. Operation time, blood loss, length of stay and complications in the Dynesys group were significantly less than that in the fusion group. Adjacent-segment degeneration in the fusion group was significantly higher than that in the Dynesys group. In addition, postoperative operated segment ROM was significantly less in the fusion group as compared to the Dynesys group. Conclusions: Our meta-analysis suggests that Dynesys system acquires comparable clinical outcomes compared to fusion in the treatment of lumbar degenerative diseases. Moreover, compared with fusion, Dynesys could remain ROM of surgical segments with less operation time, blood loss, length of stay, adjacent-segment degeneration, and lower complication. Further studies with large samples, long term follow up and well-designed are needed to assess the two procedures in the future.